1987
DOI: 10.1002/bip.360260611
|View full text |Cite
|
Sign up to set email alerts
|

Raman amide bands of type‐II β‐turns in cyclo‐(VPGVG)3 and poly‐(VPGVG), and implications for protein secondary‐structure analysis

Abstract: The cyclopentadecapeptide, c(VPGVG)3, a model structure for protein type‐II β‐turns [W. J. Cook et al. (1980) J. Am. Chem. Soc. 102, 5502–5505], has been investigated by laser Raman spectroscopy. Data obtained from both normal and deuterated crystals identify amide I, III, I′, and III′ bands characteristic of the β(II)turn. The structurally related polypentapeptide poly(VPGVG) in normal and deuterated forms has also been investigated, and exhibits the same Raman amide bands as c(VPGVG)3. The coacervate of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 19 publications
5
64
0
1
Order By: Relevance
“…Bands of interest for this work are indicated on the figure. The first fact that called our attention was that the spectrum differed only marginally from those found in the literature on aqueous solutions of the polymer 22) . Amide Raman bands, and in general all bands in the whole spectrum, are broad and spread over a wide wavenumber range.…”
Section: Raman Vibrational Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Bands of interest for this work are indicated on the figure. The first fact that called our attention was that the spectrum differed only marginally from those found in the literature on aqueous solutions of the polymer 22) . Amide Raman bands, and in general all bands in the whole spectrum, are broad and spread over a wide wavenumber range.…”
Section: Raman Vibrational Analysismentioning
confidence: 96%
“…This group has been already used as reference band elsewhere since its spectral features (area, width, shape, etc.) seem not to be affected by experimental conditions 22) . Changes in the Amide A bandwidth were also observed (Fig.…”
Section: Raman Vibrational Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…A weak splitting of this last band shows the presence of a b-turn. [18,19] After approaching the equilibrium state at the air-water interface, the band intensities do not change anymore. Comparison of inten- sities of the amide I band using s-and p-polarized light ( Figure 6) shows that the b-sheet is lying flat at the interface.…”
mentioning
confidence: 99%
“…Numerous physical characterizations* have demonstrated this transition to be an inverse temperature transition, in which the order in the polypeptide part of this twocomponent system increases as the temperature is raised through the transition. Those physical characterizations include (i) self-assembly studies, in which the polypeptide is found to assemble into several-micrometer-diameter fibers composed of fibrils that in turn are composed of approximately 50-A-diameter filaments (8-10); (ii) circular dichroism and Raman spectroscopy, in which the polypeptide chains within the coacervate are seen to have a repeating p-turn conformation (11,12); (iii) nuclear Overhauser effect studies, which demonstrate the specific hydrophobic side chain associations (ref. 13, D.W.U., D. K. Chang, R. Krishna, D. H. Huang, T. L. Trapane, and K.U.P., unpublished data); (iv) NMR studies, which show a decrease in backbone mobility as the temperature is raised through the transition under conditions of constant composition (14,15); (v) dielectric relaxation studies, which show the development of an intense, localized, Debye-type relaxation near 10 MHz requiring the development of a regular dynamic backbone conformation (16); (vi) elastomer length studies, in which the elastomer shortens to less than 45% of its low-temperature length when the temperature is raised from 20'C to 40'C (17); and (vii) studies of slow thermal denaturation at 80'C in which the circular dichroism indicates the loss of order (4), composition studies show a dramatic expulsion of water to a new composition of 68% peptide and 32% water by weight (4), and, for the elastomer, there is a decrease in length and loss of elastic modulus (ref.…”
mentioning
confidence: 99%